PENGARUH SERVANT LEADERSHIP, KOMITMEN ORGANISASIONAL DAN IKLIM ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. BPR SANTI PALA BADUNG - Ni Putu Lina Sudianingsih; Ni Nyoman Ari Novarini; Putu Ayu Sintya Saraswati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
The existence of a bank is urgently needed, one way to maintain the existence of a bank is to have competent human resources (HR) in the banking world. Human resources are the main capital as a determining factor for the progress of a company. People or humans who work in organizations with the capabilities they have are called human resources. This study aims to determine the effect of servant leadership, organizational commitment and organizational climate on employee performance at PT. BPR Santi Pala Badung with a total sample of 32 employees. The sampling technique used is saturated sampling method. Data collection methods used were observation, questionnaires, library research and interviews. The analysis technique used is multiple linear regression analysis through the SPSS version 25 program. Based on the results of the analysis, this study shows that servant leadership has a positive and significant effect on employee performance at PT. BPR Santi Pala Badung. The better the servant leadership at PT. BPR Santi Pala Badung, the better the employee performance. Organizational commitment has a positive and significant effect on employee performance at PT. BPR Santi Pala Badung. The better the organizational commitment in PT. BPR Santi Pala Badung, employee performance will increase. Organizational climate has a positive and significant effect on employee performance at PT. BPR Santi Pala Badung. The better the organizational climate in PT. BPR Santi Pala Badung, the better the employee performance.